Гендерні особливості копінг-поведінки працівників ОВС - Макаренко, П. В.; Makarenko, P. V. (Вісник Національного університету оборони України. - 2014. - Вип. 4(41). - С. 252-256, 2014)
У статті представлені результати дослідження гендерних особливостей використання різних стратегій копінг-поведінки працівниками міліції. Визначено, що у реальному професійному колективі жінки та чоловіки працівники ОВС схильні проявляти різні тенденції поведінки. З’ясовано, що у складних життєвих та професійних ситуаціях для подолання труднощів чоловіки та жінки працівники ОВС використовують однакові стратегії копінг-поведінки: планування, позитивна переоцінка і самоконтроль.

There are the results of the study of gender issues in the use of various strategies for coping behavior of police officers in the article. The theoretical analysis of the concept of coping behavior and coping strategies is presented. Based on the results of the empirical study determined that the real professional team male and female police officers tend to exhibit different trends of behavior. It was found that in difficult situations and professional difficulties to overcome male and female police officers use the same strategies coping behaviors: planning, positive reappraisal, and self-control. It was determined that women police officers in professional team striving for independence and autonomy, try to remain neutral in conflict situations and act on their own decision regardless of the views of colleagues. Men officers staff simply adopt standards and rules of the team in which they are, they avoid the inherent communication with colleagues and inclination to compromise decision-making in complex situations. Stated that when confronted with problematic situations police officers of both sexes are equally able to effectively analyze and develop strategies to solve them by planning their actions, positive reassessment and self-preservation.

В статье представлены результаты исследования гендерных особенностей использования различных стратегий копинг-поведения работниками милиции. Определено, что в реальном профессиональном коллективе женщины и мужчины сотрудники ОВД склонны проявлять различные тенденции поведения. Выяснено, что в сложных жизненных и профессиональных ситуациях для преодоления трудностей мужчины и женщины сотрудники ОВД используют одинаковые стратегии копинг-поведения: планирование, положительная переоценка и самоконтроль.
The gender-specific features of police officer’s coping-behavior
Keywords: опановуюча поведінка; копінг-поведінка; працівники органів внутрішніх справ; гендерні особливості; coping behavior; coping strategies; police officers; employee of internal affairs; gender characteristics; совладающее поведение; копинг-поведение; работники органов внутренних дел; гендерные особенности